ENDORSING PROACTIVE WORK BEHAVIOR IN TRANSMITTING GRIT AND INTERPERSONAL SKILLS INTO TASK PERFORMANCE - Irvandi Gustari; Widodo Widodo (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
Task performance is crucial to employee performance, competitive advantage, and organizational performance. Therefore, this study focuses on employee task performance based on the perspectives of grit and interpersonal skills through proactive work behavior (PWB). Research participants included 325 workers from private companies in the finance, investment, trade, and service industries sector in Indonesia. A Likert scale survey was employed to get the data. The results were derived by Partial Least Squares-based Structural Equation Modeling analysis alongside descriptive and correlational analysis. The findings demonstrated that grit, interpersonal skills, and PWB influence employees' task performance; grit and interpersonal skills affect employees' PWB; and PWB mediates the relationship between grit, interpersonal skills, and employees' task performance. This evidence supports a novel empirical paradigm about the effect of grit and interpersonal skills on task performance via the mediation of PWB. These findings offer a theoretical contribution to enhancing task performance research centered on grit, interpersonal skills, and PWB, while also presenting practical implications for organizational operations aimed at improving employee task performance through these attributes.